Simulation of homoepitaxial growth on the diamond (100) surface using detailed reaction mechanisms - Ruf, Bernhard; Behrendt, Frank; Deutschmann, Olaf; Warnatz, Jürgen (Surface science, 1996)
One-dimensional reactive-flow simulations of a hot-filament CVD-system including detailed surface reaction mechanisms for homoepitaxial diamond growth are carried out. A growth model for the diamond (100) surface based on elementary chemical reactions steps is introduced. This surface reaction scheme includes the incorporation of the CH3 radical in the diamond lattice. Homoepitaxial growth on the (100) surface is modelled for a wide range of experimental reactor parameters. The experimental growth rates are compared with simulations for two different surface reaction schemes. It is found that the scheme based on growth at monoatomic steps on the reconstructed (100) surface is more realistic. It shows qualitative agreement with experimental data, whereas the more simple mechanism for an unrealistic unreconstructed (100) surface cannot explain the surface temperature dependence of the growth rate correctly.
Elektronische Reproduktion der Druck-Ausgabe 6. April 2000
Gesehen am 09.05.2023